A study on advertising and promotions of Wheelock Place. - Khang, Tat Chung. (2012)
Due to the rise of five new malls that significantly chips at the overlapping share of the consumer segments, Wheelock Place now faces an increasingly competitive environment and tenant revenue start to fall. Wheelock Place, in the face of the lack of A&P funds, has to actively source for a way to improve consumer inflow and spending. However, the various types of marketing communication tools used in the retail industry have been at saturation levels as consumers are bombarded with different concepts and catchphrases on a constant basis. Furthermore, the overhaul of the commuting structure has affected the ways by which consumers come to Wheelock Place. In the meantime, redemption programmes held by the mall’s management do not appear effective in attracting nor retaining consumers. To address these issues, the perspectives of the management, tenants, and consumers are investigated and considered in order to develop a suitable solution. The investigation is carried out through a series of interviews with the management and the tenants, as well as consumer questionnaires. The results are then analysed to form identifiable trends/segments, namely Loyalists, High-spenders and No-income, which exhibit different characteristics which would prove beneficial to both Wheelock Place and tenants in terms of A&P resource allocation and the tailoring of their respective marketing programmes.